Moral Values of Movie “Ghostbuster: Afterlife” - Marvino Christian; Fauziah Nur (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
This research aims to describe the moral values found in the movie “Ghostbuster Afterlife ", based on the character’s behaviour and action and why they occurred in movies. The moral of a story in movies is the lesson that the story or movie teaches about how to behave in the world or what action should be used in certain situations. The method used in the research is conducted using a descriptive qualitative method which described the data from the observed people and behaviour. The research data were collected by watching the movie and identifying the data related to the study. There are 11 moral values found in the movie “Ghostbuster Afterlife”. From this research the relevance between the implications of the movie toward our own moral values is honesty. Being honest with other people will help develop our relationships with others, especially with family, friends, and loved ones will help improve life and character.